Metformin Use and Leukemia Risk in Patients With Type 2 Diabetes Mellitus - Tseng, Chin-Hsiao (Frontiers in Endocrinology, 2020)
Background: The effect of metformin on leukemia risk remained unknown. Methods: The Taiwan’s National Health Insurance database was used to enroll 610,089 newly diagnosed type 2 diabetes patients with 2 or more times of prescription of antidiabetic drugs during 1999-2009. Leukemia incidence was followed up in the patients until December 31, 2011. Cox regression incorporated with the inverse probability of treatment-weighting using propensity scores was used to estimate hazard ratios in both intention-to-treat and per-protocol analyses. Results: A total of 414,783 metformin initiators and 195,306 non-metformin initiators were enrolled. Among them, 598 and 372 patients developed new-onset leukemia after a median follow-up of 5.08 years and 6.79 years, respectively. The respective incidence rates were 26.52 and 28.40 per 100,000 person-years. The hazard ratio for metformin initiators versus non-metformin initiators was 0.943 (95% confidence interval 0.828-1.074) in the intention-to-treat analysis and was 0.852 (95% confidence interval 0.705-1.031) in the per-protocol analysis. Sensitivity analyses after excluding patients with a follow-up duration <24 and <36 months, respectively, after excluding patients with incretin-based therapies during follow-up, and in patients enrolled during two different periods of 1999-2003 and 2004-2009 consistently showed a neutral effect. However, when censoring patients at a time without regular follow-up, metformin initiators had a significantly higher risk of leukemia in the per-protocol analyses. Conclusions: Metformin use has an overall neutral effect on leukemia but a significantly higher risk cannot be excluded among patients who persistently use the drug.